2023
DOI: 10.1007/s11107-023-00992-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance of finite energy Airy Hermite Gaussian beam in strong atmospheric turbulence

Abstract: This paper presents intensity evolution of finite energy Airy Hermite Gaussian(FEAHG) beam and its scintillation performance under strong atmospheric conditions. Atmosphere is modeled utilizing split step propagation. Our results reveals that, beam evolves into elliptic shape during propagation. Point like scintillation reduction is obtained for all setting of FEAHG beam. For selected apertures less scintillation index is provided by FEAHG beam. We think that our results are used in free space optical communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Regarding this, it has been reported that scintillation mitigation is observed when finite energy Airy Hermite Gaussian beam with higher order is used [7]. A significant bit error rate reduction is obtained using Lommel beam since its scintillation is quite low [8]. In addition, the scintillation difference between Gaussian beam and Weber beam increases as turbulence strength increases [9].…”
Section: Introductionmentioning
confidence: 98%
“…Regarding this, it has been reported that scintillation mitigation is observed when finite energy Airy Hermite Gaussian beam with higher order is used [7]. A significant bit error rate reduction is obtained using Lommel beam since its scintillation is quite low [8]. In addition, the scintillation difference between Gaussian beam and Weber beam increases as turbulence strength increases [9].…”
Section: Introductionmentioning
confidence: 98%